Console Structures in Building Design and Construction - Mohhamad Kusyanto (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2026)
The console structure is one of the structural systems widely applied in building design and construction, especially to meet the need for column-free space and architectural form expression. The application of the console structure allows building elements to protrude from the main support without direct support underneath, thus providing design flexibility as well as challenges from the structural and construction side. This article aims to examine the console structure in the context of building design and construction, covering the working principles of the structure, its role in the formation of architectural design, and commonly used construction systems. The research method used is a qualitative descriptive method through literature studies of textbooks, structural planning standards, and relevant scientific articles. The results of the study indicate that the console structure has an important role in the integration between the structural system and architectural design, but requires careful planning and construction implementation to ensure the safety and performance of the building as well as sustainability. This study is expected to be an initial reference for designers and practitioners in applying the console structure appropriately in buildings.